A Review on Permian to Triassic Active or Convergent Margin in Southeasternmost Gondwanaland: Possibility of Exploration Target for Tin and Hydrocarbon Deposits in the Eastern Indonesia - Amiruddin, Amiruddin (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20094An active convergence of continental margin is probably generated in Gondwanaland during Permian to Triassic period which is characterized by the presence of magmatic and volcanic belts and back-arc ba- sins occupied respectively by Permian to Triassic rocks. The magmatic belt is occupied by peraluminous granitic plutons showing characteristics of S- type granite and is considered as tin-bearing granites. The back-arc basins are occupied by the Southern Papua and Galille-Bowen-Gunnedah-Sydney Basins. Those large basins are respectivelly filled by fluvial, fluvio- deltaic to marine Permian-Triassic sediments, which are unconformably overlain by the Jurrassic-Cretaceous marine succession. The paleomagnetic data, confirmed by flora content found in Australia and Papua, indicate that those areas initially belong to the Gondwanaland before part of them were drifted and rotated into the present day position. Tectonically, the presence of those Permian-Triassic magmatic-volcanic belts and back-arc basins in behind, indicates that at the time there were huge compressive activities: convergence of paleo-oceanic Pasific Plate moving westward, collided and subducted into the Southeastern Gondwana Continental Plate, moved relatively eastwards. This phenomenon resembles to the formation of Sumatera Tertiary tectonic zones producing back-arc basins, i.e. South Sumatera, Central, and North Sumatera Basins including the Tertiary Magmatic Arc. Concerning the similarity of Permian-Triassic geological condition of the magmatic arc and back-arc basins in Eastern Indonesia and Eastern Australia including paleoposition, paleotectonic setting, strati- graphic succession, and lithologic composition, it is suggested to carry out an increase in a more intens- ive tin exploration in the Eastern Indonesia, e.g. Bird Head area and Banggai Sula Island, and also for hydrocarbon target (coal, coalbed methane, oil and gas, and oil shale) in the Southern Papua Basin, East Indonesia. This suggestion is confirmed by cassiterite and hydrocarbon discoveries and exploitation activ- ity in the Eastern Australia and also a new seismic data of the Semai Basin a part of Southern Papua Basin. This seismic record shows a more complete stratigraphic sucession and a number of large structure traps of stratigraphic levels in which the Permian-Triassic units are included within the sequence. Â